Anthropometric and physical performance characteristics of elite male wheelchair basketball athletes - Chapman, D. D.; Fulton, S.; Gough, C. (The Journal of Strength and Conditioning Research, 2010)
Wheelchair basketball is a popular Paralympic sport; however there is a paucity of research describing the physical qualities of elite wheelchair athletes. The objective of this study was to provide anthropometric and physical performance characteristics from field tests of elite male basketball players. Data was collected during two training camps for a national wheelchair basketball squad (n = 19) as part of periodic physical conditioning evaluation. Athletes were only included in the analysis if they were free of injury and illness at the time of testing and were able to complete the entire test battery. Athletes were requested to use the same wheelchair configuration throughout each testing session. All provided written informed consent and testing was approved by the ethics committee of the Australian Institute of Sport. Anthropometric assessment (seated height, weight, arm span and [n-ary summation]4 skinfolds) and field-based tests; 20 m sprint speed, Wheelchair Illinois agility test, 10 m speed agility (left or right veer), Wheelchair basketball line drill and work capacity push test, were used to determine the physical conditioning status. All testing was performed on an indoor sprung wooden basketball court with a minimum of five minutes rest provided between tests. Strong verbal encouragement was provided to all athletes during each assessment to ensure a maximum effort. Results were examined in relation to the smallest worthwhile change for each test and relationships between variables were examined using a Pearson's correlation. There was no significant relationship between anthropometric variables of weight, arm span and [n-ary summation]4 skinfolds and performance in any of these field tests. Strong relationships between tests of short sprint duration (sprint speed, speed agility and Illinois agility) with the work capacity push test were observed. The lack of observed relationships between anthropometric variables of weight, arm span and [n-ary summation]4 skinfolds and performance in any of the field tests questions the utility of these measures in an elite wheelchair athlete population. The lack of relationship indicates that in this elite athlete population, anthropometry measures do not significantly influence the physical requirements of wheelchair basketball. Logically though strong relationships between performance tests were observed. This data provides the basis to begin an extensive profiling of elite wheelchair athletes using reliable and inexpensive field testing protocols. Interestingly the described protocols could become a resource for coaches and scientists to use theses tests as a benchmark for training program design and talent identification for elite male wheelchair basketball players.